Waterproof barrier adhesive tape in aircraft cabin and preparation method of waterproof barrier adhesive tape
By mixing polyacrylate emulsion, functionalized polysiloxane and modified graphene oxide, waterproof barrier tape in the aircraft cabin is prepared, which solves the problems of poor sealing effect and easy corrosion in the prior art, and achieves good waterproof barrier and antibacterial effects.
Patent Information
- Application Number
- CN202510106640.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing aircraft cabin sealing methods and products have problems such as poor sealing effect, complex installation and maintenance, and easy corrosion, which affects the performance and life of the equipment.
The waterproof barrier tape in the aircraft cabin was dried by mixing polyacrylate emulsion, functionalized polysiloxane and modified graphene oxide.
It achieves the waterproof barrier effect in the aircraft cabin, extends the life of the material, reduces the risk of corrosion, and improves the physical barrier properties and antibacterial properties of the material.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, in particular to a waterproof barrier tape for aircraft cabins and a preparation method thereof. Background Art
[0002] With the rapid development of my country's national defense industry, the number and increment of various types of domestic aircraft have maintained a large growth. The existing sealing methods and products have gradually exposed their defects. The sealing effect is not good, and the installation and maintenance process is cumbersome, time-consuming and labor-intensive. The poor effect of sealing products is more likely to cause corrosion of key parts of various equipment, affecting the performance and life of the equipment, and even causing accidents.
[0003] The main materials of the cabin include aluminum alloy, titanium alloy, ultra-high strength steel, magnesium alloy and composite materials. These materials play an important role in different parts of the cabin. The penetration corrosion of water vapor molecules and oxygen molecules on metal materials seriously affects the life of the cabin all the time. Water vapor and oxygen are the main factors for metal corrosion and rust in the atmosphere. When metal is exposed to a humid atmosphere, it is easy to form the electrolyte solution required for electrochemical corrosion, causing the metal to corrode. Therefore, this article introduces a waterproof barrier tape for aircraft cabins and its preparation method. Summary of the invention
[0004] The object of the present invention is to provide a waterproof barrier tape for aircraft cabin and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] A waterproof barrier tape for aircraft cabins, wherein the waterproof barrier tape for aircraft cabins is prepared by mixing polyacrylate emulsion, functionalized polysiloxane and modified graphene oxide, coating the mixture on a polyurethane film, and drying the mixture; The polyurethane film is prepared by reacting polycarbonate diol, polyethylene glycol, hydroxyethyl methacrylate, isophorone diisocyanate, 4,5-bis(hydroxymethyl)-2-phenyl-1H-imidazole and bis(hydroxymethyl)phenylphosphine, and then extruding and casting the resulting film. The modified graphene oxide is prepared by reacting graphene oxide with 2,5-dimethyl-2,5-hexanediol and 5-amino-4-imidazolecarboxamide in sequence; The functionalized polysiloxane is prepared by polymerizing trimethylmethoxysilane, dimethoxydimethylsilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, and allylmethyldimethoxysilane, and then reacting with dimethylphosphine and 1,2-epoxychlorobutane in sequence; The polyacrylate emulsion is prepared by reacting glycidyl methacrylate, methyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate.
[0006] A method for preparing a waterproof barrier tape for aircraft cabins, the method for preparing the waterproof barrier tape for aircraft cabins mainly comprising the following preparation steps: (1) adding a 2,5-dimethyl-2,5-hexanediol aqueous solution to a graphene oxide aqueous solution of 4 to 6 times the mass of the 2,5-dimethyl-2,5-hexanediol aqueous solution at a uniform speed within 8 to 10 minutes, stirring at 85 to 95°C and 200 to 300 r / min for 25 to 35 minutes, filtering, washing with deionized water for 3 to 5 times, and drying at 55 to 65°C for 22 to 26 hours to obtain pre-modified graphene oxide; mixing the pre-modified graphene oxide, phosphotungstic acid, 5-amino-4-imidazolecarboxamide and formic acid in a mass ratio of 4 to 6: 0.2 to 0.3: 1: 18 to 22, stirring at 75 to 85°C and 200 to 300 r / min for 10 to 14 hours, filtering, washing with deionized water for 3 to 5 times, and vacuum drying at 40 to 50°C for 22 to 24 hours to obtain modified graphene oxide; (2) Trimethylmethoxysilane, dimethoxydimethylsilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, allylmethyldimethoxysilane, deionized water and 36%~38% hydrochloric acid solution are mixed in a mass ratio of 1~2:16~20:5~7:10~12:30~50:1~3, stirred at 200~300r / min for 25~35min, heated to 50~60℃, continued stirring for 2.5~3.5h, and dried at 80~100℃ for 20~24h to obtain pre-modified polysiloxane; dimethylphosphine, toluene and catalyst are mixed in a mass ratio of 1:5~7:0.12~0.13 , stirring for 10-20 minutes at 95-105°C, 200-300 r / min, under nitrogen protection, uniformly adding a polysiloxane solution of equal mass of dimethyl phosphine within 5-7 hours, continuing stirring for 16-20 hours, drying at 50-70°C for 22-26 hours, washing, and vacuum drying at 50-70°C for 22-26 hours to obtain modified polysiloxane; the modified polysiloxane, sodium iodide, 1,2-epoxychlorobutane and acetone were mixed in a mass ratio of 80-100:1:20-30:400-600, reacted at 35-45°C under nitrogen protection for 46-50 hours, filtered, washed, and dried at 50-60°C for 6-8 hours to obtain functionalized polysiloxane; (3) Polycarbonate diol, polyethylene glycol and dibutyltin dilaurate are mixed uniformly in a mass ratio of 1:1:0.08-0.12, and added to isophorone diisocyanate of equal mass of polycarbonate diol at a uniform speed within 8-10 minutes, stirred at 45-55°C and 200-300 r / min for 100-140 minutes, heated to 55-65°C, and 0.2-0.3 times the mass of polycarbonate diol of bis(hydroxymethyl)phenylphosphine and 0.2-0.3 times the mass of polycarbonate diol of 4,5-di(hydroxymethyl)-2-phenyl-1H- imidazole, continue to react for 50-70 minutes, raise the temperature to 60-70°C, add 0.2-0.3 times the mass of polycarbonate diol hydroxyethyl methacrylate, continue to react for 100-140 minutes to obtain a polyurethane prepolymer; mix the polyurethane prepolymer with deionized water at a mass ratio of 1:3-4, disperse at 10000-14000 rpm for 25-35 minutes, cast into a polytetrafluoroethylene mold, use a vacuum oven to remove bubbles in the dispersion, let it stand at room temperature for 22-26 hours, and then dry at 35-45°C for 46-50 hours to obtain a polyurethane film; (4) Take 1 part of glycidyl methacrylate, 1 part of methyl methacrylate, 3-5 parts of butyl acrylate, 3-5 parts of 2-ethylhexyl acrylate, 0.1-0.2 parts of dibenzoyl peroxide, 20-30 parts of toluene and 40-60 parts of ethyl acetate by mass, mix dibenzoyl peroxide, ethyl acetate and toluene, heat to 76-80°C at 200-300 r / min, then add glycidyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate, continue stirring, heat to 90-100°C, continue stirring, add methyl methacrylate at a uniform speed within 80-100 min, heat to 95-105°C, continue stirring for 2-3 h, cool to room temperature, and prepare a polyacrylate emulsion; (5) The polyacrylate emulsion and the functionalized polysiloxane are mixed in a mass ratio of 6-8:1, heated to 80-100°C, and an equal amount of modified graphene oxide of the functionalized polysiloxane is added. The mixture is stirred at 400-600 r / min for 8-12 min, and degassed in a vacuum degassing machine at 1000-1400 r / min for 50-70 s. The mixture is coated on a polyurethane film using an I-shaped coater, allowed to stand at room temperature for 20-30 min, allowed to stand at 75-85°C for 50-70 min, and then allowed to stand at 100-110°C for 50-70 min to obtain a waterproof barrier tape for the cabin.
[0007] As an optimization, the graphene oxide aqueous solution in step (1) is prepared by uniformly mixing graphene oxide and deionized water in a mass ratio of 1:190-210.
[0008] As an optimization, the graphene oxide in step (1) is flake graphene oxide with a purity of 99.9%.
[0009] As an optimization, the 2,5-dimethyl-2,5-hexanediol aqueous solution in step (1) is prepared by uniformly mixing 2,5-dimethyl-2,5-hexanediol and deionized water in a mass ratio of 1:190-210.
[0010] As an optimization, the polysiloxane solution in step (2) is prepared by uniformly mixing pre-modified polysiloxane and toluene in a mass ratio of 1:2-3.
[0011] As an optimization, the catalyst in step (2) is triethylamine.
[0012] As an optimization, the specific operation of washing in step (2) is washing with ethanol 3 to 5 times.
[0013] As an optimization, the polycarbonate diol in step (3) is 1000 g / mol of polycarbonate diol.
[0014] As an optimization, the polyethylene glycol in step (3) is 1000 g / mol polyethylene glycol.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the waterproof barrier tape for aircraft cabins, the present invention comprises the following steps: reacting graphene oxide with 2,5-dimethyl-2,5-hexanediol and 5-amino-4-imidazolecarboxamide in sequence to obtain modified graphene oxide; reacting pre-modified polysiloxane with dimethyl phosphine and 1,2-epoxychlorobutane in sequence to obtain functionalized polysiloxane; reacting polycarbonate diol, polyethylene glycol, hydroxyethyl methacrylate, isophorone diisocyanate, 4,5-di(hydroxymethyl)-2-phenyl-1H-imidazole and bis(hydroxymethyl)phenylphosphine to obtain polyurethane particles, which are extruded and cast into films; and mixing polyacrylate emulsion, functionalized polysiloxane and modified graphene oxide, coating the mixture on the polyurethane film, and drying the mixture to obtain the waterproof barrier tape for aircraft cabins.
[0016] First, when preparing the waterproof barrier tape in the aircraft cabin, the present invention sequentially reacts graphene oxide with 2,5-dimethyl-2,5-hexanediol and 5-amino-4-imidazolecarboxamide to obtain modified graphene oxide; the graphene oxide is sequentially reacted with 2,5-dimethyl-2,5-hexanediol and 5-amino-4-imidazolecarboxamide to make the surface of the graphene oxide rich in imidazole and the surface of the graphene oxide contains conjugated rings to achieve an aging-resistant effect; the graphene oxide has a high specific surface area and a layered structure, and can form a complex network shielding structure in the material, effectively inhibiting The infiltration, penetration and diffusion of corrosive media can improve the physical barrier properties of materials. Due to its ultra-thin layer thickness, graphene oxide can fill in the defects of materials, reduce the porosity of materials, enhance the density of materials, and further delay or prevent the corrosion factors from penetrating into the surface of the substrate. It has good chemical and thermal stability, and its layer structure is stacked and staggered, which can form a maze effect in the material, effectively extending the water vapor channel, improving the density of materials, and has good physical barrier properties for small molecules, which can extend the diffusion path of corrosive media, thereby achieving a barrier effect. Secondly, the pre-modified polysiloxane is reacted with dimethyl phosphide and 1,2-epoxychlorobutane in sequence to obtain functionalized polysiloxane; trimethylmethoxysilane, dimethoxydimethylsilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane and allylmethyldimethoxysilane are polymerized to make the polysiloxane rich in epoxy groups for easy cross-linking; and then reacted with dimethyl phosphide, which can react with the double bonds contained in the polysiloxane. Organic phosphorus will form phosphoric acid during combustion, and phosphoric acid will further dehydrate to form metaphosphoric acid and polymetaphosphoric acid. These compounds have strong dehydration properties and can promote the carbonization of organic matter to form a dense carbonized layer. This carbonized layer can effectively isolate oxygen and heat, thereby preventing the spread of flames; and organic phosphorus will absorb a large amount of heat during decomposition, thereby reducing The surface temperature of the polymer is reduced, thereby slowing down the combustion rate. Organic phosphorus can form a thin glassy or liquid protective layer on the surface of the polymer. This protective layer can reduce oxygen diffusion and heat transfer, inhibit the oxidation process of carbon, and thus play a flame retardant role; finally, it reacts with 1,2-epoxychlorobutane to make the polysiloxane contain more epoxy groups and quaternary phosphonium salts. Quaternary phosphonium salts can be adsorbed on the surface of negatively charged microorganisms and penetrate into the inside of microorganisms, changing the properties of the native membrane and making the bacteria unable to move normally. The hydrophobic base dissolves the fat wall on the surface of the bacteria, thereby causing the death of the bacteria and achieving an antibacterial effect; polysiloxane will solidify immediately after contacting water, forming a strong protective layer, which can effectively prevent water from invading and achieve a waterproof barrier effect.
[0017] Finally, polycarbonate diol, polyethylene glycol, hydroxyethyl methacrylate, isophorone diisocyanate, 4,5-di(hydroxymethyl)-2-phenyl-1H-imidazole and bis(hydroxymethyl)phenylphosphine are reacted to obtain polyurethane particles, which are then extruded and cast into films; polyacrylate emulsion, functionalized polysiloxane and modified graphene oxide are mixed, coated on the polyurethane film, and dried to obtain a waterproof barrier tape for aircraft cabins; 4,5-di(hydroxymethyl)-2-phenyl-1H-imidazole and bis(hydroxymethyl)phenylphosphine are used as functional monomers to participate in the reaction to prepare polyurethane particles, phosphorus can play a flame retardant effect, and the imidazole in the polyurethane, the imidazole on the modified graphene oxide, the epoxy group in the polyacrylate emulsion and the epoxy group in the functionalized polysiloxane can be cross-linked to achieve a better bonding effect and enhance the mechanical properties of the material. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0019] Example 1 A method for preparing a waterproof barrier tape for aircraft cabins, mainly comprising the following preparation steps: (1) Graphene oxide and deionized water are mixed evenly at a mass ratio of 1:190 to prepare a graphene oxide aqueous solution; 2,5-dimethyl-2,5-hexanediol and deionized water are mixed evenly at a mass ratio of 1:190 to prepare a 2,5-dimethyl-2,5-hexanediol aqueous solution; the 2,5-dimethyl-2,5-hexanediol aqueous solution is added uniformly over 8 minutes to a graphene oxide aqueous solution with a mass of 4 times that of the 2,5-dimethyl-2,5-hexanediol aqueous solution; The mixture was stirred at 85°C and 200 r / min for 25 min, filtered, washed with deionized water for 3 times, and dried at 55°C for 22 h to obtain pre-modified graphene oxide; the pre-modified graphene oxide, phosphotungstic acid, 5-amino-4-imidazolecarboxamide and formic acid were mixed in a mass ratio of 4:0.2:1:18, stirred at 75°C and 200 r / min for 10 h, filtered, washed with deionized water for 3 times, and dried in vacuum at 40°C for 22 h to obtain modified graphene oxide; (2) Trimethylmethoxysilane, dimethoxydimethylsilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, allylmethyldimethoxysilane, deionized water and 36% hydrochloric acid solution were mixed in a mass ratio of 1:16:5:10:30:1, stirred at 200 r / min for 25 min, heated to 50°C, continued to stir for 2.5 h, and dried at 80°C for 20 h to obtain pre-modified polysiloxane; the pre-modified polysiloxane and toluene were mixed in a mass ratio of 1:2 to obtain a polysiloxane solution; dimethylphosphine, toluene and triethylamine were mixed in a mass ratio of 1:2 to obtain a polysiloxane solution; The mixture was mixed in a mass ratio of 1:5:0.12, stirred at 95°C, 200 r / min, and under nitrogen protection for 10 min, and a polysiloxane solution of equal mass of dimethyl phosphine was added at a uniform rate within 5 h, and the mixture was stirred for 16 h. The mixture was dried at 50°C for 22 h, washed with ethanol for 3 times, and vacuum dried at 50°C for 22 h to obtain a modified polysiloxane. The modified polysiloxane, sodium iodide, 1,2-epoxychlorobutane, and acetone were mixed in a mass ratio of 80:1:20:400, reacted at 35°C under nitrogen protection for 46 h, filtered, washed with ethanol for 3 times, and dried at 50°C for 6 h to obtain a functionalized polysiloxane. (3) Polycarbonate diol, polyethylene glycol and dibutyltin dilaurate were mixed in a mass ratio of 1:1:0.08, and added to isophorone diisocyanate of the same mass as polycarbonate diol at a uniform speed within 8 minutes. The mixture was stirred at 45°C and 200 r / min for 100 minutes. The temperature was raised to 55°C, and 0.2 times the mass of polycarbonate diol of bis(hydroxymethyl)phenylphosphine and 0.2 times the mass of polycarbonate diol of 4,5-di(hydroxymethyl)-2-phenyl-1- H-imidazole, continue to react for 50 minutes, heat to 60°C, add 0.2 times the mass of polycarbonate diol hydroxyethyl methacrylate, continue to react for 100 minutes to obtain a polyurethane prepolymer; mix the polyurethane prepolymer with deionized water in a mass ratio of 1:3, disperse at 10000rpm for 25 minutes, cast into a polytetrafluoroethylene mold, use a vacuum oven to remove bubbles in the dispersion, let it stand at room temperature for 22 hours, and then dry at 35°C for 46 hours to obtain a polyurethane film; (4) Take 1 part of glycidyl methacrylate, 1 part of methyl methacrylate, 3 parts of butyl acrylate, 3 parts of 2-ethylhexyl acrylate, 0.1 part of dibenzoyl peroxide, 20 parts of toluene and 40 parts of ethyl acetate by mass, mix dibenzoyl peroxide, ethyl acetate and toluene, heat to 76°C at 200 r / min, then add glycidyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate, continue stirring, heat to 90°C, continue stirring, add methyl methacrylate at a uniform speed within 80 minutes, heat to 95°C, continue stirring for 2 hours, cool to room temperature, and prepare a polyacrylate emulsion; (5) The polyacrylate emulsion and the functionalized polysiloxane were mixed in a mass ratio of 6:1, heated to 80°C, and an equal mass of modified graphene oxide of the functionalized polysiloxane was added. The mixture was stirred at 400 r / min for 8 min, and degassed in a vacuum degassing machine at 1000 r / min for 50 s. The mixture was coated on a polyurethane film using an I-shaped coater, allowed to stand at room temperature for 20 min, allowed to stand at 75°C for 50 min, and then heated to 100°C and allowed to stand for 50 min to obtain a waterproof barrier tape for the cabin.
[0020] Example 2 A method for preparing a waterproof barrier tape for aircraft cabins, mainly comprising the following preparation steps: (1) Graphene oxide and deionized water were mixed at a mass ratio of 1:200 to obtain a graphene oxide aqueous solution; 2,5-dimethyl-2,5-hexanediol and deionized water were mixed at a mass ratio of 1:200 to obtain a 2,5-dimethyl-2,5-hexanediol aqueous solution; the 2,5-dimethyl-2,5-hexanediol aqueous solution was added uniformly over 9 minutes to a graphene oxide aqueous solution with a mass of 5 times that of the 2,5-dimethyl-2,5-hexanediol aqueous solution; The mixture was stirred at 90°C and 250 r / min for 30 min, filtered, washed with deionized water for 4 times, and dried at 60°C for 24 h to obtain pre-modified graphene oxide; the pre-modified graphene oxide, phosphotungstic acid, 5-amino-4-imidazolecarboxamide and formic acid were mixed in a mass ratio of 5:0.25:1:20, stirred at 80°C and 250 r / min for 12 h, filtered, washed with deionized water for 4 times, and vacuum dried at 45°C for 23 h to obtain modified graphene oxide; (2) Trimethylmethoxysilane, dimethoxydimethylsilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, allylmethyldimethoxysilane, deionized water and 37% hydrochloric acid solution were mixed in a mass ratio of 1.5:18:6:11:40:2, stirred at 250 r / min for 30 min, heated to 55 °C, continued to stir for 3 h, and dried at 90 °C for 22 h to obtain pre-modified polysiloxane; the pre-modified polysiloxane and toluene were mixed in a mass ratio of 1:2.5 to obtain a polysiloxane solution; dimethylphosphine, toluene and triethylamine were mixed in a mass ratio of 1:2.5 to obtain a polysiloxane solution; The mixture was mixed in a mass ratio of 1:6:0.125, stirred at 100°C, 250 r / min, and under nitrogen protection for 15 min, and a polysiloxane solution of equal mass of dimethyl phosphine was added at a uniform rate within 6 h, and the mixture was stirred for 18 h. The mixture was dried at 60°C for 24 h, washed with ethanol 4 times, and vacuum dried at 60°C for 24 h to obtain a modified polysiloxane. The modified polysiloxane, sodium iodide, 1,2-epoxychlorobutane, and acetone were mixed in a mass ratio of 90:1:25:500, reacted at 40°C under nitrogen protection for 48 h, filtered, washed with ethanol 4 times, and dried at 55°C for 7 h to obtain a functionalized polysiloxane. (3) Polycarbonate diol, polyethylene glycol and dibutyltin dilaurate were mixed in a mass ratio of 1:1:0.1, and added to isophorone diisocyanate of the same mass as polycarbonate diol at a uniform speed within 9 minutes. The mixture was stirred at 50°C and 250 r / min for 120 minutes. The temperature was raised to 60°C, and 0.25 times the mass of polycarbonate diol of bis(hydroxymethyl)phenylphosphine and 0.25 times the mass of polycarbonate diol of 4,5-di(hydroxymethyl)-2-phenyl-1H -imidazole, continue to react for 60 minutes, heat to 65°C, add 0.25 times the mass of polycarbonate diol hydroxyethyl methacrylate, continue to react for 120 minutes to obtain a polyurethane prepolymer; mix the polyurethane prepolymer with deionized water at a mass ratio of 1:3.5, disperse at 12000rpm for 30 minutes, cast into a polytetrafluoroethylene mold, use a vacuum oven to remove bubbles in the dispersion, let it stand at room temperature for 24 hours, and then dry at 40°C for 48 hours to obtain a polyurethane film; (4) Take 1 part of glycidyl methacrylate, 1 part of methyl methacrylate, 4 parts of butyl acrylate, 4 parts of 2-ethylhexyl acrylate, 0.15 parts of dibenzoyl peroxide, 25 parts of toluene and 50 parts of ethyl acetate by mass, mix dibenzoyl peroxide, ethyl acetate and toluene, heat to 78°C at 250 r / min, then add glycidyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate, continue stirring, heat to 95°C, continue stirring, add methyl methacrylate at a uniform rate within 90 minutes, heat to 100°C, continue stirring for 2.5 hours, cool to room temperature, and prepare a polyacrylate emulsion; (5) The polyacrylate emulsion and the functionalized polysiloxane were mixed in a mass ratio of 7:1, heated to 90°C, and modified graphene oxide of equal mass to the functionalized polysiloxane was added. The mixture was stirred at 500 r / min for 10 min, and degassed in a vacuum degassing machine at 1200 r / min for 60 s. The mixture was coated on a polyurethane film using an I-shaped coater, allowed to stand at room temperature for 25 min, allowed to stand at 80°C for 60 min, and then heated to 105°C and allowed to stand for 60 min to obtain a cabin waterproof barrier tape.
[0021] Example 3 A method for preparing a waterproof barrier tape for aircraft cabins, mainly comprising the following preparation steps: (1) Graphene oxide and deionized water are mixed evenly at a mass ratio of 1:210 to prepare a graphene oxide aqueous solution; 2,5-dimethyl-2,5-hexanediol and deionized water are mixed evenly at a mass ratio of 1:210 to prepare a 2,5-dimethyl-2,5-hexanediol aqueous solution; the 2,5-dimethyl-2,5-hexanediol aqueous solution is added uniformly within 10 minutes to a graphene oxide aqueous solution with a mass of 6 times that of the 2,5-dimethyl-2,5-hexanediol aqueous solution; Stirring at 95°C and 300 r / min for 35 min, filtering, washing with deionized water for 5 times, and drying at 65°C for 26 h to obtain pre-modified graphene oxide; mixing pre-modified graphene oxide, phosphotungstic acid, 5-amino-4-imidazolecarboxamide and formic acid in a mass ratio of 6:0.3:1:22, stirring at 85°C and 300 r / min for 14 h, filtering, washing with deionized water for 5 times, and vacuum drying at 50°C for 24 h to obtain modified graphene oxide; (2) Trimethylmethoxysilane, dimethoxydimethylsilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, allylmethyldimethoxysilane, deionized water and 38% hydrochloric acid solution were mixed in a mass ratio of 2:20:7:12:50:3, stirred at 300 r / min for 35 min, heated to 60°C, continued to stir for 3.5 h, and dried at 100°C for 24 h to obtain pre-modified polysiloxane; the pre-modified polysiloxane and toluene were mixed in a mass ratio of 1:3 to obtain a polysiloxane solution; dimethylphosphine, toluene and triethylamine were mixed in a mass ratio of 1:3 to obtain a polysiloxane solution; The mixture was mixed at a mass ratio of 1:7:0.13, stirred at 105°C, 300 r / min, and under nitrogen protection for 20 min, and a polysiloxane solution of equal mass of dimethyl phosphine was added at a uniform rate within 7 h, and the mixture was stirred for 20 h. The mixture was dried at 70°C for 26 h, washed with ethanol 5 times, and vacuum dried at 70°C for 26 h to obtain modified polysiloxane. The modified polysiloxane, sodium iodide, 1,2-epoxychlorobutane and acetone were mixed at a mass ratio of 100:1:30:600, reacted at 45°C under nitrogen protection for 50 h, filtered, washed with ethanol 5 times, and dried at 60°C for 8 h to obtain functionalized polysiloxane. (3) Polycarbonate diol, polyethylene glycol and dibutyltin dilaurate were mixed in a mass ratio of 1:1:0.12, and added to isophorone diisocyanate of the same mass as polycarbonate diol at a uniform speed within 10 minutes. The mixture was stirred at 55°C and 300 r / min for 140 minutes. The temperature was raised to 65°C, and 0.3 times the mass of polycarbonate diol of bis(hydroxymethyl)phenylphosphine and 0.3 times the mass of polycarbonate diol of 4,5-di(hydroxymethyl)-2-phenyl-1- H-imidazole, continue to react for 70 minutes, heat to 70°C, add 0.3 times the mass of polycarbonate diol hydroxyethyl methacrylate, continue to react for 140 minutes to obtain a polyurethane prepolymer; mix the polyurethane prepolymer with deionized water in a mass ratio of 1:4, disperse at 14000rpm for 35 minutes, cast into a polytetrafluoroethylene mold, use a vacuum oven to remove bubbles in the dispersion, let it stand at room temperature for 26 hours, and then dry at 45°C for 50 hours to obtain a polyurethane film; (4) Take 1 part of glycidyl methacrylate, 1 part of methyl methacrylate, 5 parts of butyl acrylate, 5 parts of 2-ethylhexyl acrylate, 0.2 parts of dibenzoyl peroxide, 30 parts of toluene and 60 parts of ethyl acetate by mass, mix dibenzoyl peroxide, ethyl acetate and toluene, heat to 80°C at 300 r / min, then add glycidyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate, continue stirring, heat to 100°C, continue stirring, add methyl methacrylate at a uniform rate within 100 minutes, heat to 105°C, continue stirring for 3 hours, cool to room temperature, and prepare a polyacrylate emulsion; (5) The polyacrylate emulsion and the functionalized polysiloxane were mixed in a mass ratio of 8:1, heated to 100°C, and modified graphene oxide of equal mass to the functionalized polysiloxane was added. The mixture was stirred at 600 r / min for 12 min, and degassed in a vacuum degassing machine at 1400 r / min for 70 s. The mixture was coated on a polyurethane film using an I-shaped coater, allowed to stand at room temperature for 30 min, allowed to stand at 85°C for 70 min, and then heated to 110°C and allowed to stand for 70 min to obtain a cabin waterproof barrier tape.
[0022] Comparative Example 1 A method for preparing a waterproof barrier tape for aircraft cabins, mainly comprising the following preparation steps: (1) Trimethylmethoxysilane, dimethoxydimethylsilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, allylmethyldimethoxysilane, deionized water and 37% hydrochloric acid solution were mixed in a mass ratio of 1.5:18:6:11:40:2, stirred at 250 r / min for 30 min, heated to 55°C, continued to stir for 3 h, and dried at 90°C for 22 h to obtain pre-modified polysiloxane; the pre-modified polysiloxane and toluene were mixed in a mass ratio of 1:2.5 to obtain a polysiloxane solution; dimethylphosphine, toluene and triethylamine were mixed in a mass ratio of 1:2.5 to obtain a polysiloxane solution; The mixture was mixed in a mass ratio of 1:6:0.125, stirred at 100°C, 250 r / min, and under nitrogen protection for 15 min, and a polysiloxane solution of equal mass of dimethyl phosphine was added at a uniform rate within 6 h, and the mixture was stirred for 18 h. The mixture was dried at 60°C for 24 h, washed with ethanol 4 times, and vacuum dried at 60°C for 24 h to obtain a modified polysiloxane. The modified polysiloxane, sodium iodide, 1,2-epoxychlorobutane, and acetone were mixed in a mass ratio of 90:1:25:500, reacted at 40°C under nitrogen protection for 48 h, filtered, washed with ethanol 4 times, and dried at 55°C for 7 h to obtain a functionalized polysiloxane. (2) Polycarbonate diol, polyethylene glycol and dibutyltin dilaurate were mixed uniformly in a mass ratio of 1:1:0.1, and added to isophorone diisocyanate of equal mass of polycarbonate diol at a uniform speed within 9 minutes. The mixture was stirred at 50°C and 250 r / min for 120 minutes. The temperature was raised to 60°C, and 0.25 times the mass of polycarbonate diol of bis(hydroxymethyl)phenylphosphine and 0.25 times the mass of polycarbonate diol of 4,5-di(hydroxymethyl)-2-phenyl-1H -imidazole, continue to react for 60 minutes, heat to 65°C, add 0.25 times the mass of polycarbonate diol hydroxyethyl methacrylate, continue to react for 120 minutes to obtain a polyurethane prepolymer; mix the polyurethane prepolymer with deionized water at a mass ratio of 1:3.5, disperse at 12000rpm for 30 minutes, cast into a polytetrafluoroethylene mold, use a vacuum oven to remove bubbles in the dispersion, let it stand at room temperature for 24 hours, and then dry at 40°C for 48 hours to obtain a polyurethane film; (3) Take 1 part of glycidyl methacrylate, 1 part of methyl methacrylate, 4 parts of butyl acrylate, 4 parts of 2-ethylhexyl acrylate, 0.15 parts of dibenzoyl peroxide, 25 parts of toluene and 50 parts of ethyl acetate by mass, mix dibenzoyl peroxide, ethyl acetate and toluene, heat to 78°C at 250 r / min, then add glycidyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate, continue stirring, heat to 95°C, continue stirring, add methyl methacrylate at a uniform speed within 90 minutes, heat to 100°C, continue stirring for 2.5 hours, cool to room temperature, and prepare a polyacrylate emulsion; (4) The polyacrylate emulsion and the functionalized polysiloxane were mixed in a mass ratio of 7:1, heated to 90°C, and an equal mass of graphene oxide of the functionalized polysiloxane was added. The mixture was stirred at 500 r / min for 10 min, and degassed in a vacuum degassing machine at 1200 r / min for 60 s. The mixture was coated on a polyurethane film using an I-shaped coater, allowed to stand at room temperature for 25 min, allowed to stand at 80°C for 60 min, and then heated to 105°C and allowed to stand for 60 min to obtain a cabin waterproof barrier tape.
[0023] Comparative Example 2 A method for preparing a waterproof barrier tape for aircraft cabins, mainly comprising the following preparation steps: (1) Trimethylmethoxysilane, dimethoxydimethylsilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, allylmethyldimethoxysilane, deionized water and 37% hydrochloric acid solution were mixed in a mass ratio of 1.5:18:6:11:40:2, stirred at 250 r / min for 30 min, heated to 55°C, continued to stir for 3 h, and dried at 90°C for 22 h to obtain pre-modified polysiloxane; the pre-modified polysiloxane and toluene were mixed in a mass ratio of 1:2.5 to obtain a polysiloxane solution; dimethylphosphine, toluene and triethylamine were mixed in a mass ratio of 1:2.5 to obtain a polysiloxane solution; The mixture was mixed in a mass ratio of 1:6:0.125, stirred at 100°C, 250 r / min, and under nitrogen protection for 15 min, and a polysiloxane solution of equal mass of dimethyl phosphine was added at a uniform rate within 6 h, and the mixture was stirred for 18 h. The mixture was dried at 60°C for 24 h, washed with ethanol 4 times, and vacuum dried at 60°C for 24 h to obtain a modified polysiloxane. The modified polysiloxane, sodium iodide, 1,2-epoxychlorobutane, and acetone were mixed in a mass ratio of 90:1:25:500, reacted at 40°C under nitrogen protection for 48 h, filtered, washed with ethanol 4 times, and dried at 55°C for 7 h to obtain a functionalized polysiloxane. (2) Polycarbonate diol, polyethylene glycol and dibutyltin dilaurate were mixed uniformly in a mass ratio of 1:1:0.1, and added to isophorone diisocyanate of equal mass of polycarbonate diol at a uniform speed within 9 minutes. The mixture was stirred at 50°C and 250 r / min for 120 minutes. The temperature was raised to 60°C, and 0.25 times the mass of polycarbonate diol of bis(hydroxymethyl)phenylphosphine and 0.25 times the mass of polycarbonate diol of 4,5-di(hydroxymethyl)-2-phenyl-1H -imidazole, continue to react for 60 minutes, heat to 65°C, add 0.25 times the mass of polycarbonate diol hydroxyethyl methacrylate, continue to react for 120 minutes to obtain a polyurethane prepolymer; mix the polyurethane prepolymer with deionized water at a mass ratio of 1:3.5, disperse at 12000rpm for 30 minutes, cast into a polytetrafluoroethylene mold, use a vacuum oven to remove bubbles in the dispersion, let it stand at room temperature for 24 hours, and then dry at 40°C for 48 hours to obtain a polyurethane film; (3) Take 1 part of glycidyl methacrylate, 1 part of methyl methacrylate, 4 parts of butyl acrylate, 4 parts of 2-ethylhexyl acrylate, 0.15 parts of dibenzoyl peroxide, 25 parts of toluene and 50 parts of ethyl acetate by mass, mix dibenzoyl peroxide, ethyl acetate and toluene, heat to 78°C at 250 r / min, then add glycidyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate, continue stirring, heat to 95°C, continue stirring, add methyl methacrylate at a uniform speed within 90 minutes, heat to 100°C, continue stirring for 2.5 hours, cool to room temperature, and prepare a polyacrylate emulsion; (4) The polyacrylate emulsion and the functionalized polysiloxane were mixed in a mass ratio of 7:1, heated to 90°C, stirred at 500 r / min for 10 min, degassed in a vacuum degassing machine at 1200 r / min for 60 s, coated on a polyurethane film using an I-shaped coater, left at room temperature for 25 min, left at 80°C for 60 min, and then heated to 105°C for 60 min to obtain a cabin waterproof barrier tape.
[0024] Comparative Example 3 A method for preparing a waterproof barrier tape for aircraft cabins, mainly comprising the following preparation steps: (1) Graphene oxide and deionized water were mixed at a mass ratio of 1:200 to obtain a graphene oxide aqueous solution; 2,5-dimethyl-2,5-hexanediol and deionized water were mixed at a mass ratio of 1:200 to obtain a 2,5-dimethyl-2,5-hexanediol aqueous solution; the 2,5-dimethyl-2,5-hexanediol aqueous solution was added uniformly over 9 minutes to a graphene oxide aqueous solution with a mass of 5 times that of the 2,5-dimethyl-2,5-hexanediol aqueous solution; The mixture was stirred at 90°C and 250 r / min for 30 min, filtered, washed with deionized water for 4 times, and dried at 60°C for 24 h to obtain pre-modified graphene oxide; the pre-modified graphene oxide, phosphotungstic acid, 5-amino-4-imidazolecarboxamide and formic acid were mixed in a mass ratio of 5:0.25:1:20, stirred at 80°C and 250 r / min for 12 h, filtered, washed with deionized water for 4 times, and vacuum dried at 45°C for 23 h to obtain modified graphene oxide; (2) Trimethylmethoxysilane, dimethoxydimethylsilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, allylmethyldimethoxysilane, deionized water and 37% hydrochloric acid solution were mixed in a mass ratio of 1.5:18:6:11:40:2, stirred at 250 r / min for 30 min, heated to 55 °C, continued to stir for 3 h, and dried at 90 °C for 22 h to obtain a pre-modified polysiloxane; The modified polysiloxane and toluene are uniformly mixed in a mass ratio of 1:2.5 to obtain a polysiloxane solution; dimethyl phosphide, toluene and triethylamine are mixed in a mass ratio of 1:6:0.125, stirred at 100°C, 250r / min, and nitrogen protection for 15min, and an equal mass of polysiloxane solution of dimethyl phosphide is uniformly added within 6h, and stirring is continued for 18h, dried at 60°C for 24h, washed with ethanol 4 times, and vacuum dried at 60°C for 24h to obtain a modified polysiloxane; (3) Polycarbonate diol, polyethylene glycol and dibutyltin dilaurate were mixed in a mass ratio of 1:1:0.1, and added to isophorone diisocyanate of the same mass as polycarbonate diol at a uniform speed within 9 minutes. The mixture was stirred at 50°C and 250 r / min for 120 minutes. The temperature was raised to 60°C, and 0.25 times the mass of polycarbonate diol of bis(hydroxymethyl)phenylphosphine and 0.25 times the mass of polycarbonate diol of 4,5-di(hydroxymethyl)-2-phenyl-1H -imidazole, continue to react for 60 minutes, heat to 65°C, add 0.25 times the mass of polycarbonate diol hydroxyethyl methacrylate, continue to react for 120 minutes to obtain a polyurethane prepolymer; mix the polyurethane prepolymer with deionized water at a mass ratio of 1:3.5, disperse at 12000rpm for 30 minutes, cast into a polytetrafluoroethylene mold, use a vacuum oven to remove bubbles in the dispersion, let it stand at room temperature for 24 hours, and then dry at 40°C for 48 hours to obtain a polyurethane film; (4) Take 1 part of glycidyl methacrylate, 1 part of methyl methacrylate, 4 parts of butyl acrylate, 4 parts of 2-ethylhexyl acrylate, 0.15 parts of dibenzoyl peroxide, 25 parts of toluene and 50 parts of ethyl acetate by mass, mix dibenzoyl peroxide, ethyl acetate and toluene, heat to 78°C at 250 r / min, then add glycidyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate, continue stirring, heat to 95°C, continue stirring, add methyl methacrylate at a uniform rate within 90 minutes, heat to 100°C, continue stirring for 2.5 hours, cool to room temperature, and prepare a polyacrylate emulsion; (5) The polyacrylate emulsion and the modified polysiloxane were mixed in a mass ratio of 7:1, heated to 90°C, and modified graphene oxide in an amount equal to the mass of the modified polysiloxane was added. The mixture was stirred at 500 r / min for 10 min, and degassed in a vacuum degassing machine at 1200 r / min for 60 s. The mixture was coated on a polyurethane film using an I-shaped coater, allowed to stand at room temperature for 25 min, allowed to stand at 80°C for 60 min, and then heated to 105°C and allowed to stand for 60 min to obtain a cabin waterproof barrier tape.
[0025] Comparative Example 4 A method for preparing a waterproof barrier tape for aircraft cabins, mainly comprising the following preparation steps: (1) Graphene oxide and deionized water were mixed at a mass ratio of 1:200 to obtain a graphene oxide aqueous solution; 2,5-dimethyl-2,5-hexanediol and deionized water were mixed at a mass ratio of 1:200 to obtain a 2,5-dimethyl-2,5-hexanediol aqueous solution; the 2,5-dimethyl-2,5-hexanediol aqueous solution was added uniformly over 9 minutes to a graphene oxide aqueous solution with a mass of 5 times that of the 2,5-dimethyl-2,5-hexanediol aqueous solution; The mixture was stirred at 90°C and 250 r / min for 30 min, filtered, washed with deionized water for 4 times, and dried at 60°C for 24 h to obtain pre-modified graphene oxide; the pre-modified graphene oxide, phosphotungstic acid, 5-amino-4-imidazolecarboxamide and formic acid were mixed in a mass ratio of 5:0.25:1:20, stirred at 80°C and 250 r / min for 12 h, filtered, washed with deionized water for 4 times, and vacuum dried at 45°C for 23 h to obtain modified graphene oxide; (2) trimethylmethoxysilane, dimethoxydimethylsilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, allylmethyldimethoxysilane, deionized water and 37% hydrochloric acid solution were mixed in a mass ratio of 1.5:18:6:11:40:2, stirred at 250 r / min for 30 min, heated to 55 ° C, continued to stir for 3 h, and dried at 90 ° C for 22 h to obtain pre-modified polysiloxane; (3) Polycarbonate diol, polyethylene glycol and dibutyltin dilaurate were mixed in a mass ratio of 1:1:0.1, and added to isophorone diisocyanate of the same mass as polycarbonate diol at a uniform speed within 9 minutes. The mixture was stirred at 50°C and 250 r / min for 120 minutes. The temperature was raised to 60°C, and 0.25 times the mass of polycarbonate diol of bis(hydroxymethyl)phenylphosphine and 0.25 times the mass of polycarbonate diol of 4,5-di(hydroxymethyl)-2-phenyl-1H -imidazole, continue to react for 60 minutes, heat to 65°C, add 0.25 times the mass of polycarbonate diol hydroxyethyl methacrylate, continue to react for 120 minutes to obtain a polyurethane prepolymer; mix the polyurethane prepolymer with deionized water at a mass ratio of 1:3.5, disperse at 12000rpm for 30 minutes, cast into a polytetrafluoroethylene mold, use a vacuum oven to remove bubbles in the dispersion, let it stand at room temperature for 24 hours, and then dry at 40°C for 48 hours to obtain a polyurethane film; (4) Take 1 part of glycidyl methacrylate, 1 part of methyl methacrylate, 4 parts of butyl acrylate, 4 parts of 2-ethylhexyl acrylate, 0.15 parts of dibenzoyl peroxide, 25 parts of toluene and 50 parts of ethyl acetate by mass, mix dibenzoyl peroxide, ethyl acetate and toluene, heat to 78°C at 250 r / min, then add glycidyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate, continue stirring, heat to 95°C, continue stirring, add methyl methacrylate at a uniform rate within 90 minutes, heat to 100°C, continue stirring for 2.5 hours, cool to room temperature, and prepare a polyacrylate emulsion; (5) The polyacrylate emulsion and the pre-modified polysiloxane were mixed in a mass ratio of 7:1, heated to 90°C, and modified graphene oxide in an amount equal to the mass of the pre-modified polysiloxane was added. The mixture was stirred at 500 r / min for 10 min, and degassed in a vacuum degassing machine at 1200 r / min for 60 s. The mixture was coated on a polyurethane film using an I-shaped coater, allowed to stand at room temperature for 25 min, allowed to stand at 80°C for 60 min, and then heated to 105°C and allowed to stand for 60 min to obtain a cabin waterproof barrier tape.
[0026] Comparative Example 5 A method for preparing a waterproof barrier tape for aircraft cabins, mainly comprising the following preparation steps: (1) Graphene oxide and deionized water were mixed at a mass ratio of 1:200 to obtain a graphene oxide aqueous solution; 2,5-dimethyl-2,5-hexanediol and deionized water were mixed at a mass ratio of 1:200 to obtain a 2,5-dimethyl-2,5-hexanediol aqueous solution; the 2,5-dimethyl-2,5-hexanediol aqueous solution was added uniformly over 9 minutes to a graphene oxide aqueous solution with a mass of 5 times that of the 2,5-dimethyl-2,5-hexanediol aqueous solution; The mixture was stirred at 90°C and 250 r / min for 30 min, filtered, washed with deionized water for 4 times, and dried at 60°C for 24 h to obtain pre-modified graphene oxide; the pre-modified graphene oxide, phosphotungstic acid, 5-amino-4-imidazolecarboxamide and formic acid were mixed in a mass ratio of 5:0.25:1:20, stirred at 80°C and 250 r / min for 12 h, filtered, washed with deionized water for 4 times, and vacuum dried at 45°C for 23 h to obtain modified graphene oxide; (2) Polycarbonate diol, polyethylene glycol and dibutyltin dilaurate were mixed uniformly in a mass ratio of 1:1:0.1, and added to isophorone diisocyanate of equal mass of polycarbonate diol at a uniform speed within 9 minutes. The mixture was stirred at 50°C and 250 r / min for 120 minutes. The temperature was raised to 60°C, and 0.25 times the mass of polycarbonate diol of bis(hydroxymethyl)phenylphosphine and 0.25 times the mass of polycarbonate diol of 4,5-di(hydroxymethyl)-2-phenyl-1H -imidazole, continue to react for 60 minutes, heat to 65°C, add 0.25 times the mass of polycarbonate diol hydroxyethyl methacrylate, continue to react for 120 minutes to obtain a polyurethane prepolymer; mix the polyurethane prepolymer with deionized water at a mass ratio of 1:3.5, disperse at 12000rpm for 30 minutes, cast into a polytetrafluoroethylene mold, use a vacuum oven to remove bubbles in the dispersion, let it stand at room temperature for 24 hours, and then dry at 40°C for 48 hours to obtain a polyurethane film; (3) Take 1 part of glycidyl methacrylate, 1 part of methyl methacrylate, 4 parts of butyl acrylate, 4 parts of 2-ethylhexyl acrylate, 0.15 parts of dibenzoyl peroxide, 25 parts of toluene and 50 parts of ethyl acetate by mass, mix dibenzoyl peroxide, ethyl acetate and toluene, heat to 78°C at 250 r / min, then add glycidyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate, continue stirring, heat to 95°C, continue stirring, add methyl methacrylate at a uniform speed within 90 minutes, heat to 100°C, continue stirring for 2.5 hours, cool to room temperature, and prepare a polyacrylate emulsion; (4) The polyacrylate emulsion was heated to 90°C, and modified graphene oxide in an amount of 0.143 times the mass of the polyacrylate emulsion was added. The mixture was stirred at 500 r / min for 10 min, and degassed in a vacuum degassing machine at 1200 r / min for 60 s. The mixture was coated on a polyurethane film using an I-shaped coater, and allowed to stand at room temperature for 25 min, allowed to stand at 80°C for 60 min, and then heated to 105°C and allowed to stand for 60 min to obtain a cabin waterproof barrier tape.
[0027] Comparative Example 6 A method for preparing a waterproof barrier tape for aircraft cabins, mainly comprising the following preparation steps: (1) Graphene oxide and deionized water were mixed at a mass ratio of 1:200 to obtain a graphene oxide aqueous solution; 2,5-dimethyl-2,5-hexanediol and deionized water were mixed at a mass ratio of 1:200 to obtain a 2,5-dimethyl-2,5-hexanediol aqueous solution; the 2,5-dimethyl-2,5-hexanediol aqueous solution was added uniformly over 9 minutes to a graphene oxide aqueous solution with a mass of 5 times that of the 2,5-dimethyl-2,5-hexanediol aqueous solution; The mixture was stirred at 90°C and 250 r / min for 30 min, filtered, washed with deionized water for 4 times, and dried at 60°C for 24 h to obtain pre-modified graphene oxide; the pre-modified graphene oxide, phosphotungstic acid, 5-amino-4-imidazolecarboxamide and formic acid were mixed in a mass ratio of 5:0.25:1:20, stirred at 80°C and 250 r / min for 12 h, filtered, washed with deionized water for 4 times, and vacuum dried at 45°C for 23 h to obtain modified graphene oxide; (2) Trimethylmethoxysilane, dimethoxydimethylsilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, allylmethyldimethoxysilane, deionized water and 37% hydrochloric acid solution were mixed in a mass ratio of 1.5:18:6:11:40:2, stirred at 250 r / min for 30 min, heated to 55 °C, continued to stir for 3 h, and dried at 90 °C for 22 h to obtain pre-modified polysiloxane; the pre-modified polysiloxane and toluene were mixed in a mass ratio of 1:2.5 to obtain a polysiloxane solution; dimethylphosphine, toluene and triethylamine were mixed in a mass ratio of 1:2.5 to obtain a polysiloxane solution; The mixture was mixed in a mass ratio of 1:6:0.125, stirred at 100°C, 250 r / min, and under nitrogen protection for 15 min, and a polysiloxane solution of equal mass of dimethyl phosphine was added at a uniform rate within 6 h, and the mixture was stirred for 18 h. The mixture was dried at 60°C for 24 h, washed with ethanol 4 times, and vacuum dried at 60°C for 24 h to obtain a modified polysiloxane. The modified polysiloxane, sodium iodide, 1,2-epoxychlorobutane, and acetone were mixed in a mass ratio of 90:1:25:500, reacted at 40°C under nitrogen protection for 48 h, filtered, washed with ethanol 4 times, and dried at 55°C for 7 h to obtain a functionalized polysiloxane. (3) Polycarbonate diol, polyethylene glycol and dibutyltin dilaurate were mixed in a mass ratio of 1:1:0.1, and added to isophorone diisocyanate of the same mass as polycarbonate diol at a uniform speed within 9 minutes. The mixture was stirred at 50°C and 250 r / min for 120 minutes. The temperature was raised to 60°C, and 0.25 times the mass of polycarbonate diol of 2-phenyl-1,3-propanediol and 0.25 times the mass of polycarbonate diol of 4,5-di(hydroxymethyl)-2-phenyl- 1H-imidazole, continue to react for 60 minutes, heat to 65°C, add 0.25 times the mass of polycarbonate diol hydroxyethyl methacrylate, continue to react for 120 minutes to obtain a polyurethane prepolymer; mix the polyurethane prepolymer with deionized water at a mass ratio of 1:3.5, disperse at 12000rpm for 30 minutes, cast into a polytetrafluoroethylene mold, use a vacuum oven to remove bubbles in the dispersion, let it stand at room temperature for 24 hours, and then dry at 40°C for 48 hours to obtain a polyurethane film; (4) Take 1 part of glycidyl methacrylate, 1 part of methyl methacrylate, 4 parts of butyl acrylate, 4 parts of 2-ethylhexyl acrylate, 0.15 parts of dibenzoyl peroxide, 25 parts of toluene and 50 parts of ethyl acetate by mass, mix dibenzoyl peroxide, ethyl acetate and toluene, heat to 78°C at 250 r / min, then add glycidyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate, continue stirring, heat to 95°C, continue stirring, add methyl methacrylate at a uniform rate within 90 minutes, heat to 100°C, continue stirring for 2.5 hours, cool to room temperature, and prepare a polyacrylate emulsion; (5) The polyacrylate emulsion and the functionalized polysiloxane were mixed in a mass ratio of 7:1, heated to 90°C, and modified graphene oxide of equal mass to the functionalized polysiloxane was added. The mixture was stirred at 500 r / min for 10 min, and degassed in a vacuum degassing machine at 1200 r / min for 60 s. The mixture was coated on a polyurethane film using an I-shaped coater, allowed to stand at room temperature for 25 min, allowed to stand at 80°C for 60 min, and then heated to 105°C and allowed to stand for 60 min to obtain a cabin waterproof barrier tape.
[0028] Basic performance test of adhesive tape The hardness was tested according to ASTM D2240, and the peel strength was tested according to ASTM D3330.
[0029]
[0030] From the comparison of experimental data, it can be found that the aircraft cabin waterproof barrier tape prepared by the present invention has good basic performance.
[0031] Test Example 1 Flame retardancy test: tested according to FAR25.853 test standard. The results are shown in Table 1.
[0032] Table 1
[0033] From the comparison of the experimental data in Table 1, it can be found that the aircraft cabin waterproof barrier tape prepared by the present invention has good flame retardancy.
[0034] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 1, it can be found that the afterburning time, burning length and dripping burning time of Examples 1, 2 and 3 are shorter than those of Comparative Example 2, which indicates that after the graphene oxide is compounded with other flame retardant materials, it is decomposed by heat to produce a variety of non-combustible gases. These gases can isolate oxygen from contact with combustible gases on the one hand, and dilute oxygen on the other hand, blocking the continuous combustion conditions and playing a flame retardant role; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the afterburning time, burning length and dripping burning time of Examples 1, 2 and 3 are shorter than those of Comparative Example 4, which indicates that dimethyl phosphorus can react with the double bonds contained in polysiloxane, and organic phosphorus will form phosphoric acid during the combustion process, and phosphoric acid will further dehydrate to form metaphosphoric acid and polymetaphosphoric acid. These compounds have strong dehydration properties and can promote the carbonization of organic matter to form a dense carbonized layer. This carbonized layer can effectively isolate oxygen and heat, thereby preventing the spread of flames; and organic phosphorus will absorb a large amount of heat during the decomposition process, thereby reducing the surface temperature of the polymer, so that the surface temperature of the polymer is reduced, thereby slowing down the combustion speed. Organic phosphorus can form a thin glassy or liquid protective layer on the surface of the polymer, which can reduce oxygen diffusion and heat transfer, inhibit the oxidation process of carbon, and thus play a flame retardant role; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 5, it can be found that the afterburning time, burning length and dripping burning time of Examples 1, 2 and 3 are shorter than those of Comparative Example 5, which indicates that silicon dioxide residues will be formed during the combustion of polysiloxane. These residues can delay the volatilization of decomposition products and reduce the amount of volatiles available for combustion in the gas phase, thereby reducing the heat fed back to the polymer surface. In addition, these residues can also insulate the underlying polymer surface to prevent the external heat flux from being introduced. Polysiloxane will leave inorganic silicon dioxide residues at high temperatures. These residues have high thermal stability and can form a hard shell layer during the combustion process, covering the surface of the combustible material to prevent molten dripping, hindering the organic matter generated by the thermal decomposition of the internal polymer material from diffusing to the combustion zone, and have a good heat insulation effect, thereby achieving a flame retardant effect. From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 6, it can be found that the afterburning time, burning length and dripping burning time of Examples 1, 2 and 3 are shorter than those of Comparative Example 6, which shows that adding phosphorus-containing organic matter to the polyurethane film can effectively enhance the flame retardancy of the material. Test Example 2 Aging test According to the national standard GB / T7124-2008, 2×5cm cardboards were glued together with adhesive tape, and the paper samples were dried in an electric constant temperature blast drying oven. The HP digital push-pull force gauge was connected to the computer, and the test was started. The force gauge was rotated slowly and the curve trend was observed until the tape and paper were separated. The test was stopped and the initial maximum tension was recorded. The adhesive sample was aged for three days at a temperature of 70°C and a humidity of 100%. The maximum tension after aging was tested again, and the viscosity retention rate was calculated. The viscosity retention rate = maximum tension after aging / initial maximum tension × 100%. The results are shown in Table 2.
[0035] Table 2
[0036] From the comparison of the experimental data in Table 2, it can be found that the aircraft cabin waterproof barrier tape prepared by the present invention has good aging resistance.
[0037] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 2, it can be found that the viscosity retention rates of Examples 1, 2, 3 are greater than those of Comparative Example 1, which indicates that the graphene oxide is reacted with 2,5-dimethyl-2,5-hexanediol and 5-amino-4-imidazolecarboxamide in sequence, so that the surface of the graphene oxide is rich in conjugated rings, thereby achieving an aging-resistant effect.
[0038] Test Example 3 Antimicrobial testing According to QB / T2591-2003, the selected bacteria were Staphylococcus aureus and Escherichia coli. The results are shown in Table 3.
[0039] Table 3
[0040] From the comparison of the experimental data in Table 3, it can be found that the aircraft cabin waterproof barrier tape prepared by the present invention has good antibacterial ability.
[0041] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3 in Table 3, it can be found that the antibacterial rates of Examples 1, 2, 3 are greater than those of Comparative Example 3, which indicates that the modified polysiloxane reacts with 2-epoxychlorobutane to contain quaternary phosphonium salts, which can be adsorbed on the surface of negatively charged microorganisms and penetrate into the interior of microorganisms, changing the properties of the native membrane, making the bacteria unable to move normally, and the hydrophobic base dissolves the fat wall on the surface of the bacteria, thereby causing the death of the bacteria and achieving the antibacterial effect; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the antibacterial rates of Examples 1, 2, 3 are greater than those of Comparative Example 4, which shows that graphene oxide can interact with biomacromolecules such as enzymes and proteins in bacteria, affecting their normal functions and metabolic pathways. This interference may cause bacterial metabolic disorders, thereby inhibiting bacterial growth and reproduction, and even causing bacterial death. Test Example 4 Waterproof barrier test Water vapor transmission rate: Water vapor transmission rate was tested according to ASTM F1249-20. The results are shown in Table 4.
[0042] Table 4
[0043] From the comparison of the experimental data in Table 4, it can be found that the aircraft cabin waterproof barrier tape prepared by the present invention has a good waterproof barrier effect.
[0044] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 4, it can be found that the water vapor permeability of Examples 1, 2, 3 is smaller than that of Comparative Example 2, which shows that graphene oxide can fill the defects of the material, reduce the porosity of the material, enhance the density of the material, and further delay or prevent the corrosion factor from penetrating into the surface of the substrate. In addition, it has good chemical and thermal stability, and its layer structure is stacked and staggered, which can form a maze effect in the material, effectively extending the water vapor channel, improving the density of the material, and having good physical barrier properties for small molecules, which can extend the diffusion path of the corrosive medium, thereby achieving a barrier effect and reducing the water vapor permeability of the material. From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 5, it can be found that the water vapor permeability of Examples 1, 2, 3 is lower than that of Comparative Example 5, which shows that the polysiloxane will solidify immediately after contacting with moisture to form a solid protective layer, which can effectively prevent moisture intrusion and reduce the water vapor permeability of the material.
[0045] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A waterproof barrier tape for aircraft cabins, characterized in that: The aircraft cabin waterproof barrier tape is prepared by mixing polyacrylate emulsion, functionalized polysiloxane and modified graphene oxide, coating the mixture on a polyurethane film, and drying the mixture. The polyurethane film is prepared by reacting polycarbonate diol, polyethylene glycol, hydroxyethyl methacrylate, isophorone diisocyanate, 4,5-bis(hydroxymethyl)-2-phenyl-1H-imidazole and bis(hydroxymethyl)phenylphosphine, and then extruding and casting the resulting film. The modified graphene oxide is prepared by reacting graphene oxide with 2,5-dimethyl-2,5-hexanediol and 5-amino-4-imidazolecarboxamide in sequence; The functionalized polysiloxane is prepared by polymerizing trimethylmethoxysilane, dimethoxydimethylsilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, and allylmethyldimethoxysilane, and then reacting with dimethylphosphine and 1,2-epoxychlorobutane in sequence; The polyacrylate emulsion is prepared by reacting glycidyl methacrylate, methyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate.
2. A method for preparing a waterproof barrier tape for aircraft cabins, characterized in that: The method for preparing the waterproof barrier tape in an aircraft cabin comprises the following preparation steps: (1) adding a 2,5-dimethyl-2,5-hexanediol aqueous solution to a graphene oxide aqueous solution of 4 to 6 times the mass of the 2,5-dimethyl-2,5-hexanediol aqueous solution at a uniform speed within 8 to 10 minutes, stirring at 85 to 95°C and 200 to 300 r / min for 25 to 35 minutes, filtering, washing with deionized water for 3 to 5 times, and drying at 55 to 65°C for 22 to 26 hours to obtain pre-modified graphene oxide; mixing the pre-modified graphene oxide, phosphotungstic acid, 5-amino-4-imidazolecarboxamide and formic acid in a mass ratio of 4 to 6: 0.2 to 0.3: 1: 18 to 22, stirring at 75 to 85°C and 200 to 300 r / min for 10 to 14 hours, filtering, washing with deionized water for 3 to 5 times, and vacuum drying at 40 to 50°C for 22 to 24 hours to obtain modified graphene oxide; (2) Mix trimethylmethoxysilane, dimethoxydimethylsilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, allylmethyldimethoxysilane, deionized water and 36%~38% hydrochloric acid solution in a mass ratio of 1~2:16~20:5~7:10~12:30~50:1~3, stir at 200~300r / min for 25~35min, heat to 50~60℃, continue stirring for 2.5~3.5h, and heat at 80~100 ℃ and dried for 20-24h to obtain pre-modified polysiloxane; dimethyl phosphide, toluene and catalyst were mixed in a mass ratio of 1:5-7:0.12-0.13, stirred for 10-20min at 95-105℃, 200-300r / min, under nitrogen protection, dimethyl phosphide and polysiloxane solution of equal mass were added at a uniform rate within 5-7h, stirred for 16-20h, dried at 50-70℃ for 22-26h, washed, and vacuum dried at 50-70℃ for 22-26h to obtain modified polysiloxane; The modified polysiloxane, sodium iodide, 1,2-epoxychlorobutane and acetone are mixed in a mass ratio of 80-100:1:20-30:400-600, reacted at 35-45°C under nitrogen protection for 46-50 hours, filtered, washed, and dried at 50-60°C for 6-8 hours to obtain a functionalized polysiloxane; (3) Polycarbonate diol, polyethylene glycol and dibutyltin dilaurate are mixed uniformly in a mass ratio of 1:1:0.08-0.12, and added to isophorone diisocyanate of equal mass of polycarbonate diol at a uniform speed within 8-10 minutes, stirred at 45-55°C and 200-300 r / min for 100-140 minutes, heated to 55-65°C, and 0.2-0.3 times the mass of polycarbonate diol of bis(hydroxymethyl)phenylphosphine and 0.2-0.3 times the mass of polycarbonate diol of 4,5-di(hydroxymethyl)-2-phenyl-1H- imidazole, continue to react for 50-70 minutes, raise the temperature to 60-70°C, add 0.2-0.3 times the mass of polycarbonate diol hydroxyethyl methacrylate, continue to react for 100-140 minutes to obtain a polyurethane prepolymer; mix the polyurethane prepolymer with deionized water at a mass ratio of 1:3-4, disperse at 10000-14000 rpm for 25-35 minutes, cast into a polytetrafluoroethylene mold, use a vacuum oven to remove bubbles in the dispersion, let it stand at room temperature for 22-26 hours, and then dry at 35-45°C for 46-50 hours to obtain a polyurethane film; (4) Take 1 part of glycidyl methacrylate, 1 part of methyl methacrylate, 3-5 parts of butyl acrylate, 3-5 parts of 2-ethylhexyl acrylate, 0.1-0.2 parts of dibenzoyl peroxide, 20-30 parts of toluene and 40-60 parts of ethyl acetate by mass, mix dibenzoyl peroxide, ethyl acetate and toluene, heat to 76-80°C at 200-300 r / min, then add glycidyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate, continue stirring, heat to 90-100°C, continue stirring, add methyl methacrylate at a uniform speed within 80-100 min, heat to 95-105°C, continue stirring for 2-3 h, cool to room temperature, and prepare a polyacrylate emulsion; (5) The polyacrylate emulsion and the functionalized polysiloxane are mixed in a mass ratio of 6-8:1, heated to 80-100°C, and an equal amount of modified graphene oxide of the functionalized polysiloxane is added. The mixture is stirred at 400-600 r / min for 8-12 min, and degassed in a vacuum degassing machine at 1000-1400 r / min for 50-70 s. The mixture is coated on a polyurethane film using an I-shaped coater, allowed to stand at room temperature for 20-30 min, allowed to stand at 75-85°C for 50-70 min, and then allowed to stand at 100-110°C for 50-70 min to obtain a waterproof barrier tape for the cabin.
3. The method for preparing a waterproof barrier tape for aircraft cabin according to claim 2, characterized in that: The graphene oxide aqueous solution in step (1) is prepared by uniformly mixing graphene oxide and deionized water in a mass ratio of 1:190-210.
4. The method for preparing a waterproof barrier tape for aircraft cabin according to claim 2, characterized in that: The graphene oxide in step (1) is flaky graphene oxide with a purity of 99.9%.
5. The method for preparing a waterproof barrier tape for aircraft cabin according to claim 2, characterized in that: The 2,5-dimethyl-2,5-hexanediol aqueous solution in step (1) is prepared by uniformly mixing 2,5-dimethyl-2,5-hexanediol and deionized water in a mass ratio of 1:190-210.
6. The method for preparing a waterproof barrier tape for aircraft cabin according to claim 2, characterized in that: The polysiloxane solution in step (2) is prepared by uniformly mixing pre-modified polysiloxane and toluene in a mass ratio of 1:2-3.
7. The method for preparing a waterproof barrier tape for aircraft cabin according to claim 2, characterized in that: The catalyst in step (2) is triethylamine.
8. The method for preparing a waterproof barrier tape for aircraft cabin according to claim 2, characterized in that: The specific operation of washing in step (2) is washing with ethanol 3 to 5 times.
9. The method for preparing a waterproof barrier tape for aircraft cabin according to claim 2, characterized in that: The polycarbonate diol in step (3) is 1000 g / mol of polycarbonate diol.
10. The method for preparing a waterproof barrier tape for aircraft cabin according to claim 2, characterized in that: The polyethylene glycol in step (3) is 1000 g / mol polyethylene glycol.
Citation Information
Patent Citations
Adhesives and sealants comprising ester based on 2-propylheptanol
CN102741373A